2016
DOI: 10.4236/gep.2016.49010
|View full text |Cite
|
Sign up to set email alerts
|

Moist Potential Vorticity Vector for Diagnosis of Heavy Rainfall Events in Tanzania

Abstract: In this paper, we modify the convective vorticity vector (CVV) defined as a cross product of absolute vorticity and gradient of equivalent potential temperature to moist potential vorticity vector () MPVV defined as a cross product of absolute vorticity (a ζ) and the gradient of the moist-air entropy potential temperature (s θ). The patterns of () MPVV are compared with the patterns of heavy rainfall events that occurred over different regions in Tanzania on 20 th to 22 nd December, 2011 and on 5 th to 8 th Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…WRF is a non-hydrostatic, next-generation mesoscale NWP model that can simulate the complete set of atmospheric processes with optional adjustments to physics schemes, initialized boundary conditions and data assimilation [44]. This study adopted a similar WRF domain as used in the previous studies [39,[44][45][46][47].…”
Section: Domain Setup Configuration and Data Descriptionmentioning
confidence: 99%
“…WRF is a non-hydrostatic, next-generation mesoscale NWP model that can simulate the complete set of atmospheric processes with optional adjustments to physics schemes, initialized boundary conditions and data assimilation [44]. This study adopted a similar WRF domain as used in the previous studies [39,[44][45][46][47].…”
Section: Domain Setup Configuration and Data Descriptionmentioning
confidence: 99%
“…Gao et al (2004) suggested the use of Convective Vorticity Vector (CVV) while studying deep convection over the tropics. However CVV is defined using the gradient of equivalent potential temperature which is conserved only under moist adiabatic and frictionless atmospheric flow (Luhunga et al, 2016). Since the atmosphere is nonuniformly saturated, CVV cannot be used to study non-uniformly saturated atmospheric flow and fulfill at the same time the dry air and moist air conservative property (Luhunga et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In Tanzania, some studies have been conducted using WRF model such as Luhunga et al [7]; Kondowe et al [20] and Mlonganile et al [21]. Kondowe 2) Which combination of physical parameterization schemes accurately simulated the extreme rainfall event?…”
Section: Introductionmentioning
confidence: 99%
“…Extreme rainfall events that often occur in Dar es Salaam coastal city are influenced by variations of climate due to its physical topography, monsoon winds and ocean influences (Indian ocean) [6] [7]. About 8% of its land lies below 10 m above mean sea level and considering the low-lying nature of the coastal areas in the city, climate change and sea-level rise present additional flood major weather-related threats to the population, infrastructure and other scio-economic development in the coastal zone [8] [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation